Transformation geometry under simple shear - A.M. Dumansky; M.Y. Rusin; V.I. Nepovinnykh (Учёные записки Казанского университета: Серия Физико-математические науки)
Transformation geometry under simple shear has been analyzed. For this purpose, the mathematical apparatus of the nonlinear theory of elasticity has been used. The sequence of transformations under simple shear has been investigated. Comparison with polar decomposition has been performed. The regions of compression and extension in the deformation ellipse have been determined. It has been shown that a simple shift can be represented in the form of successive actions of rotation, deformation and rotation.